2009
DOI: 10.1017/s113874160000216x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Spanish Version of the Situational Motivation Scale (EMSI) in the Educational Context

Abstract: The purpose of the present research was to translate into Spanish and analyze the psychometricA properties of the Situational Motivation Scale (SIMS). The participants were 373 undergraduate students (126 males and 247 females). Factor validity was tested via confirmatory factor analysis. Based on factor loadings and modification indexes, the SIMS was reduced to a 14-item model. This respecification showed adequate internal consistency and construct validity. The multistep analysis of invariance revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 22 publications
2
49
0
10
Order By: Relevance
“…Prior research shows a direct relationship between intrinsic motivation and positive consequences, whereas the less self-determined kinds of motivation (amotivation and external regulation) lead to more negative consequences (Martín-Albo et al, 2009;Vallerand, 1997). These relations indicate that students who feel pleasure and satisfaction when performing an academic task may have higher levels of persistence to continue to carry out the task in the future, and vice versa.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Prior research shows a direct relationship between intrinsic motivation and positive consequences, whereas the less self-determined kinds of motivation (amotivation and external regulation) lead to more negative consequences (Martín-Albo et al, 2009;Vallerand, 1997). These relations indicate that students who feel pleasure and satisfaction when performing an academic task may have higher levels of persistence to continue to carry out the task in the future, and vice versa.…”
Section: Discussionmentioning
confidence: 96%
“…The joint use of CIF and MoCAS is the experimental group and the three control groups instructed students: in a traditional form, in a collaborative form, and collaboratively with CIF (but without the support given by MoCAS). To conduct the evaluation, we measured self-determination and the four dimensions of motivational by means of the Situational Motivation Scale (SIMS) developed by Guay, Vallerand, and Blanchard (2000), in its Spanish adaptation and validation (EMSI, see Martín-Albo, Núñez, & Navarro, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…La traducción se realizó siguiendo la estrategia de traducción inversa en la misma línea que estudios anteriores (Martín-Albo, Núñez y Navarro, 2009;Núñez, Martín-Albo y Navarro, 2005).…”
Section: Discussionunclassified
“…Also, all studies reported herein were conducted with French-Canadian participants from the Province of Quebec, Canada. It should be noted, however, that past research with scales assessing the three IM in other cultures have supported the tridimensional IM structure (e.g., Martín-Albo, Núñez, & Navarro, 2009). Nevertheless, the cross-cultural invariance of the TMIM should be tested.…”
Section: Limitationsmentioning
confidence: 93%